The Effect of Disc Displacement on Temporomandibular Joint Morphology in Patients with Disc Displacement - Yurttaş, Melike; Bozdemir, Esin; Evrimler, Şehnaz (Journal of Dentistry Indonesia, 2022)
Objective: To examine the morphological properties of temporomandibular joint structures by magnetic resonance imaging (MRI) on patients with and without disc displacement (DD). Methods: Thirty-eight patients with disc displacement and 13 patients without disc displacement were included. Age, gender, and clinical findings such as pain, joint sounds of patients were recorded. The patients were classified as anterior disc displacement with reduction (ADDWR) group, anterior disc displacement without reduction (ADDWoR) group, and control group on MRI. Disc morphology was categorized as biconcave, hemiconvex, biconvex, biplanar, or folded. Condyle morphology was characterized as convex, angled, flat, or rounded. Articular eminence morphology was classified as sigmoid, flattened, box, or deformed. A one-way analysis of variance was used to establish the differences between the values. Results: Biconcave disc and sigmoid articular eminence were the greatest incidence both in ADDWR and control group, folded disc and deformed articular eminence were the most in ADDWoR group. The most frequent types of condyle in DD and control group were flattened and convex, respectively. Statistical difference was found between pain and articular eminence morphology (p=0.02). The statistical difference regarding articular disc (p=0.001) and articular eminence morphology (p=0.02) was determined among the groups. A significant difference between condyle morphology and the presence of self-reported bruxism was detected (p= 0.03). Conclusion: The morphological characteristics of the articular disc and articular eminence are related to DD. It can be said that the morphological changes of temporomandibular joint structures point to DD.